Primary health care for people with an intellectual disability: an exploration of demographic characteristics and reasons for encounters from the BEACH programme. Issue 11 (9th June 2016) - Weise, J.; Pollack, A.; Britt, H.; Trollor, J. N.
Abstract: Background: People with an intellectual disability (ID) have complex and different patterns of healthcare needs. Poor participation in primary health care contributes to the high levels of undetected and unmanaged health issues and premature deaths of people with an ID. Limited research is available on the characteristics of people with an ID, their reasons for consulting general practitioners (GPs), and if these differ to people without an ID. Gaining such insights may provide an avenue to better understand patterns of primary care use and potential gaps in usage by people with an ID given their complex health profile compared with people without an ID. Method: A secondary analysis of data collected January 2003 to December 2012 from The Bettering the Evaluation and Care of Health programme was used. Participant characteristics and their reasons for encounter, pre‐ and post‐age‐sex standardisation, at all GP encounters with people identified in the encounter record as having an ID ('ID' encounters, n = 690) were compared with those at 'non‐ID' encounters ( n = 970 641). Statistical significance was tested with chi‐squared statistics or 95% confidence intervals as appropriate. Results: This study identified significant differences in participant characteristics and their reasons for consulting GPs at ID encounters compared with non‐ID encounters. Participants at ID encounters had a skewed demography, an over‐representation of presentations for psychological, social and 'general and unspecified' reasons, and an under‐representation of presentations for core physical health and preventive health measures. Administrative rather than medically related reasons dominated presentations to general practice at ID encounters. Conclusion: There are significant differences in the characteristics of participants and their reasons for presentation to general practice in Australia for participants at ID encounters compared with non‐ID encounters. This work suggests that there is a difference in service use patterns between these two groups. These findings may suggest that people with an ID experience barriers to participating in essential primary healthcare services.